2021
DOI: 10.1097/corr.0000000000002064
|View full text |Cite
|
Sign up to set email alerts
|

Is the Virtual Reality Fundamentals of Arthroscopic Surgery Training Program a Valid Platform for Resident Arthroscopy Training?

Abstract: Background Training in arthroscopy is associated with a steep learning curve for trainees and bears risks for patients. Virtual reality (VR) arthroscopy simulation platforms seek to overcome this and to provide a safe environment for surgical learners. The Fundamentals of Arthroscopic Surgery Training (FAST) program is one such platform. It is currently not known whether the VR FAST program can be employed as a useful teaching or examination tool to assess the basic arthroscopic skills of surgical trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…During basic virtual reality arthroscopic tasks, such as interacting with shapes, movement metrics had less success for differentiating users by experience level [76,84], although camera and grasper path length metrics collected during a virtual reality Tetris game showed orthopaedic faculty perform equivalently with the left and right hands, whereas residents lacked ambidexterity [68] (Table 2).…”
Section: Surgical Tasks Other Than Arthroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…During basic virtual reality arthroscopic tasks, such as interacting with shapes, movement metrics had less success for differentiating users by experience level [76,84], although camera and grasper path length metrics collected during a virtual reality Tetris game showed orthopaedic faculty perform equivalently with the left and right hands, whereas residents lacked ambidexterity [68] (Table 2).…”
Section: Surgical Tasks Other Than Arthroscopymentioning
confidence: 99%
“…After full-text review, we included 27 studies investigating the use of film review in orthopaedics including five randomized controlled trials [8, 9, 21, 36, 47] and 22 observational studies [3, 11, 12, 15, 20, 23, 24, 30, 41, 44, 50-52, 56, 61, 64, 65, 69, 77, 78, 81, 82]. We included 28 studies investigating the use of motion analysis in orthopaedics, including four randomized controlled trials [40, 58, 62, 70] and 24 observational studies [2, 7, 13, 14, 17, 18, 32, 38, 39, 43, 49, 57, 63, 67, 68, 71-73, 75, 76, 83, 84, 89, 90].…”
Section: Essential Elementsmentioning
confidence: 99%
“…Unfortunately, despite the recognised potential, the adoption of VR and other reality technologies in orthopaedics has lagged behind other surgical specialities [ 31 , 32 , 33 ]. While there have been notable advancements in the integration of VR for arthroscopic surgeries [ 34 , 35 , 36 , 37 ], the evolution of VR technologies for bone fracture procedures has followed a more modest course [ 31 ]. The present review aims to describe the state of the art on VR systems for orthopaedic trauma procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several different platforms one can use, their effectiveness is difficult to verify [5], and like any other technology or product, there will be various platforms or vendors that will require validation prior to adoption. In this study, Vaghela and colleagues [6] prospectively recruited orthopaedic interns (novices), residents (intermediates), and fellows and attendings (experts) to complete the VR Fundamentals of Arthroscopic Surgery Training (FAST) program over a 1-year period from four major orthopaedic training programs on a voluntary basis. Surgeons of any arthroscopic experience were included, and only those with prior experience on the VR FAST program were excluded.…”
mentioning
confidence: 99%
“…Using these methods, the authors found that six of eight VR FAST modules lacked construct validity, and they found no correlation between arthroscopic experience and ambidextrous performance. Two modules demonstrated construct validity; however, refinement and expansion of the modules was deemed necessary with further validation in large prospective trials so that pass-fail thresholds can be set for use in high-stakes examinations [6]. In my opinion, the true value of this technology in the future is to have it complement in vivo training that residents/fellows receive.…”
mentioning
confidence: 99%